2020
DOI: 10.1038/s41366-020-0561-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal obesity on placental transcriptome and morphology associated with fetal growth restriction in mice

Abstract: Background In utero exposure to obesity is consistently associated with increased risk of metabolic disease, obesity and cardiovascular dysfunction in later life despite the divergence of birth weight outcomes. The placenta plays a critical role in offspring development and long-term health, as it mediates the crosstalk between the maternal and fetal environments. However, its phenotypic and molecular modifications in the context of maternal obesity associated with fetal growth restriction (FGR) remain poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
2
12
0
1
Order By: Relevance
“…Maternal obesity during pregnancy is associated with an increased risk of both small and large for gestational age babies [ 35 ]. Consistent with previous studies in the model [ 16 , 36 , 37 ], we observed growth restriction followed by catch-up growth in offspring exposed to maternal obesity. The combination of low birth weight and accelerated postnatal growth is associated with long-term adverse effects on offspring cardiometabolic health in human studies [ 38 , 39 , 40 , 41 ] and animal models [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Maternal obesity during pregnancy is associated with an increased risk of both small and large for gestational age babies [ 35 ]. Consistent with previous studies in the model [ 16 , 36 , 37 ], we observed growth restriction followed by catch-up growth in offspring exposed to maternal obesity. The combination of low birth weight and accelerated postnatal growth is associated with long-term adverse effects on offspring cardiometabolic health in human studies [ 38 , 39 , 40 , 41 ] and animal models [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…[61] In both human and animal studies, MO reduces vascularity and constrains blood flow in the placenta. [62,63] Consistently, we found that MO decreased the expression of oxygen transporters, the hemoglobin-related genes, and increased the expression of Hif1𝛼 during embryonic myogenesis, suggesting a general hypoxic state with MO. Chronic hypoxia stabilizes HIF1A, which up-regulates the expression of glycolytic genes while suppressing genes involved in oxidative metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…Mechanistic insight into how reduced labyrinthine area might occur comes from recent transcriptomic analyses from our laboratory showing downregulation of transcripts involved in labyrinthine development in placentas from obese dams (De Barros Mucci et al . 2020). We observed a strong correlation between reduced labyrinthine area, increased placental impedance (as measured by the PPI; Gudmundsson et al .…”
Section: Discussionmentioning
confidence: 99%